Robot-assisted laparoscopic partial nephrectomy: Contemporary results over a wide range of tumor complexity - Martin H. Umbehr; Simon Jenni; Boris Fischer; Matthias Zimmermann; Klaus Steigmiller; Michael Müntener (Current Urology)
Abstract. Background. Partial nephrectomy (PN) is considered the gold standard surgical treatment for renal masses < 7cm in size (T1 tumors). Since the introduction of the robotic-assisted laparoscopic PN (raPN) in high-volume centers, it has been increasingly adapted and standardized by urologists worldwide. There is growing evidence that the robot-assisted laparoscopic technique is associated with superior outcomes compared to those of open and conventional laparoscopic techniques. This study aimed to summarize the contemporary outcome data of raPN for renal tumors with varying degrees of complexity and to assess whether the outcomes reported from high-volume centers are reproducible in a limited caseload setting. Materials and methods. This was a retrospective study of a single surgeon's experience, including 123 consecutive patients undergoing raPN at our institution. Ultimately, 110 patients were included in the analysis. Basic characteristics, tumor complexity as described by the RENAL score, complications described by the Clavien-Dindo classification system, and functional and oncological outcomes were assessed and analyzed statistically. Results. Of the 110 patients, 27 (24%), 61 (55%), and 23 (21%) had low, intermediate, and high degrees of complexity, respectively, according to the RENAL score. A cancer-negative surgical margin was achieved in 108 (97%) patients. A total of 70 (64%) patients had no loss of renal function, while 20 (27%) had minimal loss of renal function. Complications of > 3 Clavien-Dindo classification during the first 30 postoperative days occurred in 5 (5%) patients. The 3 complexity groups were found to have significantly different ischemia time: Low, 8 minutes (interquartile range [IQR], 8–9.5); Intermediate, 12 minutes (IQR, 10–13); and High, 15.5 minutes (IQR, 11.25–18.75) (p < 0.001). There were no significant differences between the groups. Conclusions. Contemporary standards for raPN are safe and reproducible. Adherence to the technique reported by centers of excellence yielded comparable results with regard to tumor control, preservation of renal function, and complication rates in lower-volume settings.